2021
DOI: 10.1002/alz.12545
|View full text |Cite
|
Sign up to set email alerts
|

Clinical reporting following the quantification of cerebrospinal fluid biomarkers in Alzheimer's disease: An international overview

Abstract: Introduction:The current practice of quantifying cerebrospinal fluid (CSF) biomarkers as an aid in the diagnosis of Alzheimer's disease (AD) varies from center to center. For a same biochemical profile, interpretation and reporting of results may differ, which can lead to misunderstandings and raises questions about the commutability of tests. Methods:We obtained a description of (pre-)analytical protocols and sample reports from 40 centers worldwide. A consensus approach allowed us to propose harmonized comme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 41 publications
0
18
0
Order By: Relevance
“…We acknowledge as the main limitation of our study the relatively small number of pre-AD and SMC-Ctrl cases, which could have hampered the inferences made on biomarker comparisons. However, the study was intended as a first exploratory step, given the difficulty in recruiting subjects with pre-AD 24. Moreover, the inclusion of Dis-Ctrl patients with moderately elevated t-tau levels might have led to underestimate the diagnostic accuracy of t-tau in comparison to β-syn.…”
Section: Discussionmentioning
confidence: 99%
“…We acknowledge as the main limitation of our study the relatively small number of pre-AD and SMC-Ctrl cases, which could have hampered the inferences made on biomarker comparisons. However, the study was intended as a first exploratory step, given the difficulty in recruiting subjects with pre-AD 24. Moreover, the inclusion of Dis-Ctrl patients with moderately elevated t-tau levels might have led to underestimate the diagnostic accuracy of t-tau in comparison to β-syn.…”
Section: Discussionmentioning
confidence: 99%
“…A recent survey of 40 laboratories across 15 countries31 indicated that cut-points are more similar across centres (but still not exactly the same) when automated assays are used, and this may in part relate to differences in preanalytical conditions but also to differences in the populations served. This study proposed a harmonisation of reporting of CSF AD biomarkers according to the eight different combinations that may be derived when the axes of amyloid, t-tau and p-tau are interpreted using centre-specific binary cut-points.…”
Section: Interpreting Biomarker Resultsmentioning
confidence: 99%
“…The field is justifiably excited about the impact that blood tests will have— widespread access to diagnosis based on biological definition of the disease. Presently, CSF and neuroimaging biomarker assessments are limited mostly to Europe, North America, and Australia, cutting off most of the world accounting for > 80% of the global population [ 16, 17 ]. Even in these three continents, access to biomarker-supported dementia care is not universal; access to biomarker testing is limited by factors such as the availability of specialized imaging facilities or clinicians trained to perform lumbar punctures, willingness to undergo minimally invasive sampling or radiation exposure, and the financial capacity to afford the cost [ 3 ].…”
mentioning
confidence: 99%